The G-7 and the post-2015 process: role and deliverables - Kathrin Berensmann; Silke Weinlich (Deutsches Institut für Entwicklungspolitik (DIE), 2015)
At the upcoming G7 Summit held in Elmau, G7 members should seize the opportunity and push for a successful outcome of the major multilateral events of 2015 dealing with development finance (Addis Ababa), the post-2015 agenda for sustainable development (New York) and climate change (Paris). We identify opportunities for action at three different levels. The G7 should introduce changes at home with a significant global impact: (i) G7 leaders should commit themselves to formulate national, time-bound plans for implementation of the universal post-2015 agenda that are linked to existing national processes such as sustainable development policies and strategies; (ii) they should be frontrunners in tackling unsustainable consumption and production patterns and (iii) specify national contributions on how to limit global warming to 2°C. The G7 should support sustainable development in low- and middle-income countries (LICs and MICs): (i) The G7 should scale up support for national public health systems in LICs and help create a health contingency fund; (ii) reconfirm and specify commitments to contribute to global public finance, including official development assistance (ODA) and climate finance and (iii) promote the transfer and development of technology for LICs and MICs. At the global level the G7 should promote global rules for global commons: (i) the G7 should implement reforms of the international financial architecture; (ii) advance the reform of the international tax system by promoting multilateral agreements to foster international cooperation among tax authorities and (iii) encourage an enabling international trade system for developing countries including a development friendly Transatlantic Trade and Investment Partnership (TTIP) and Trans-Pacific Partnership (TPP). The post-2015 agenda for sustainable development reaffirms the universality of human rights and other core G7 values. While the current draft proposal of the Sustainable Development Goals (SDGs) is not perfect, it could trigger urgent collective action which is needed now to maintain and secure prosperity and wellbeing of current and future generations within planetary boundaries. Furthermore, the sustainable development agenda provides an example of how to deal with collective problems: in a rules-based partnership, based on ideas of fairness, equity and common but differentiated responsibilities. The G7 must play their part and help the negotiations succeed.
Keywords: 330; Agenda 2030; Regionale + globale + transnationale Governance